Perspectives on Cognition, Translation, and Translators - Séguinot, Candace (TTR)

(untitled) (Association canadienne de traductologie, 2017)
Looking back on the past thirty years, this article traces the development of our understanding of the translation process, how we study it, how we have moved from essentialism to an appreciation of variation and context, what we’ve learned about how the mind stores and accesses language, and how the specifics of the translating environment affects the work of the professional translator.